Small field output correction factors of the microSilicon detector and a deeper understanding of their origin by quantifying perturbation factors. Issue 7 (13th April 2020) - Weber, Carolin; Kranzer, Rafael; Weidner, Jan; Kröninger, Kevin; Poppe, Björn; Looe, Hui Khee; Poppinga, Daniela
Abstract : Purpose: The aim of this study is the experimental and Monte Carlo‐based determination of small field correction factors for the unshielded silicon detector microSilicon for a standard linear accelerator as well as the Cyberknife System. In addition, a detailed Monte Carlo analysis has been performed by modifying the detector models stepwise to study the influences of the detector's components. Methods: Small field output correction factors have been determined for the new unshielded silicon diode detector, microSilicon (type 60023, PTW Freiburg, Germany) as well as for the predecessors Diode E (type 60017, PTW Freiburg, Germany) and Diode SRS (type 60018, PTW Freiburg, Germany) for a Varian TrueBeam linear accelerator at 6 MV and a Cyberknife system. For the experimental determination, an Exradin W1 scintillation detector (Standard Imaging, Middleton, USA) has been used as reference. The Monte Carlo simulations have been performed with EGSnrc and phase space files from IAEA as well as detector models according to manufacturer blueprints. To investigate the influence of the detector's components, the detector models have been modified stepwise. Results: The correction factors for the smallest field size investigated at the TrueBeam linear accelerator (equivalent dosimetric square field side length Sclin = 6.3 mm) are 0.983 and 0.939 for the microSilicon and Diode E, respectively. At the Cyberknife system, the correction factors of the microSilicon are 0.967 at the smallest 5‐mm collimator compared to 0.928 for the Diode SRS. Monte Carlo simulations show comparable results from the measurements and literature. Conclusion: The microSilicon (type 60023) detector requires less correction than its predecessors, Diode E (type 60017) and Diode SRS (type 60018). The detector housing has been demonstrated to cause the largest perturbation, mainly due to the enhanced density of the epoxy encapsulation surrounding the silicon chip. This density has been rendered more water equivalent in case of the microSilicon detector to minimize the associated perturbation. The sensitive volume itself has been shown not to cause observable field size‐dependent perturbation except for the volume‐averaging effect, where the slightly larger diameter of the sensitive volume of the microSilicon (1.5 mm) is still small at the smallest field size investigated with corrections <2%. The new microSilicon fulfils the 5% correction limit recommended by the TRS 483 for output factor measurements at all conditions investigated in this work.